Аналіз ринку недержавного пенсійного страхування в Україні: соціально-економічний вимір - Зеленко, Н. М.; Зеленко, В. А.; Zelenko, N. M.; Zelenko, V. A. (Видавництво Львівської політехніки, 2019)
Проаналізовано ключові зміни у функціонуванні системи недержавного пенсійного страхування в Україні, а також особливості функціонування недержавних пенсійних фондів та компаній зі страхування життя. Виконано розрахунок ємності ринку пенсійного страхування та окреслено перспективи його подальшого розвитку. Проведено порівняльний аналіз участі роботодавців та працівників у пенсійних програмах. Визначено позитивні та негативні аспекти пропонованих нововведень, зроблено відповідні висновки, надано рекомендації щодо участі у добровільній компоненті пенсійної системи України.

This article is devoted to the research of socio-economic aspects of private pension insurance in Ukraine. Article goals: 1) analyze the functioning of private pension market and life insurance by using a comparative assessment of statistical datae; 2) calculate the relevant analytical indicators that characterize the potential options for the further development of private pension provision; 3) sum up, draw conclusions and recommendations. In this article, the authors analyze the core changes in the functioning of private pension system insurance in Ukraine. The most important problem hampering the development of private pension provision system is the rejection of it as an alternative to the state system. Another problem that hinders the spread of this type of financial services in Ukraine is the low financial awareness of the people, while the degree of spread of financial services in Ukraine is lower than in the European Union. The features of the functioning of private pension funds and life insurance companies are analyzed. In 2018, private pension funds showed the better growth rates of accumulated resources in comparison with insurance companies, almost in 2.3 times. Size of their retirement benefits, was three times more than insurance companies. However, in general for 2017–2018 private pension funds and life insurance companies showed a similar increase in the number of attracted persons and the amount of accumulated resources. A comprehensive assessment of all the indicators surveyed during this period indicates that private pension funds are somewhat more stable in their activities than life insurance companies. The capacity of the pension insurance market has been calculated and indicated on the prospects for its further development. So the level of pension activity of the people in 2018 ranges near 0.05. Accordingly, the potential development of the private pension insurance market is 0.95. The number of potential participants in the near future can potentially increase up to 10 times, the volume of attracted financial resources may increase even more, as a person can pay contributions to several NPFs or insurance companies, and the amount of contributions may increase. A comparative analysis of the participation of employers and employees in privte pension funds and life insurance companies has been conducted, in which the respective advantages and disadvantages for both spheres has been highlighted. The results indicate that managers of Ukrainian enterprises are significantly more involved in voluntary pension programs than their employees. Therefore, in order to promote and develop private pension insurance, attracting employers should be priority (through corporate life insurance and privat pension provision programs). The results of the study of theoretical and practical materials allowed to identify the positive and negative aspects of the proposed innovations, to draw up relevant conclusions, and to make recommendations on participation in the voluntary component of the pension system of Ukraine. In general, in the conditions of constant instability of the domestic socio-economic system, the development of private pension insurance in the near future is quite problematic to predict.
Analysis of the private pension insurance market in Ukraine: socio-economic dimension
Keywords: пенсійне страхування; пенсійна система; пенсійна реформа; пенсійний вік; страховий стаж; недержавне пенсійне страхування; недержавний пенсійний фонд; компанія зі страхування життя; pension insurance; pension system; pension reform; retirement age; insurance record; private pension insurance; private pension fund; life insurance company; 336.233.021; 368.914](477)